Π‐Conjugated Macrocycles Bearing Angle‐Strained Alkynes. Issue 12 (16th December 2019) - Miki, Koji; Ohe, Kouichi
Abstract: Angle‐strained alkyne‐containing π‐conjugated macrocycles are attractive compounds both in functional materials chemistry and biochemistry. Their interesting reactivity as well as photophysical and supramolecular properties have been revealed in the past three decades. This review highlights the recent advances in angle‐strained alkyne‐containing π‐conjugated macrocycles, especially their synthetic methods, the bond angles of alkynes (∠sp at C≡C−C), and their functions. The theoretical and experimental research on cyclo[ n ]carbons and para ‐cyclophynes consisting of ethynylenes and para ‐phenylenes are mainly summarized. Related macrocycles bearing other linkers, such as ortho ‐phenylenes, meta ‐phenylenes, heteroaromatics, biphenyls, extended aromatics, are also overviewed. Bond angles of strained alkynes in π‐conjugated macrocycles, which are generable, detectable, and isolable, are summarized at the end of this review. Abstract : Alkynes in ring systems : Angle‐strained alkynes show specific reactivity and properties. An overview of angle‐strained alkynes in π‐conjugated macrocycles is presented. Their synthetic methods and transformations, photophysical, and supramolecular properties, and bond angles are summarized.